Aging and Poverty in Africa and the Role of Social Pensions - Subbarao, Kalanidhi (World Bank, Washington, DC, 2012)
In many low income African countries, three factors are placing an undue burden on the elderly: 1) the burden on the elderly has enormously increased with the increase in mortality of prime age adults due to the HIV-AIDS pandemic and regional conflicts; 2) the traditional safety net of the extended family has become ineffective and unreliable for the elderly; and, 3) in a few countries, the elderly are called upon to shoulder the responsibility of the family as they became the principal breadwinners, and caregivers for young children. While a number of studies have examined the welfare consequences of these developments on children, few studies have systematically analyzed the poverty situation among the elderly (relative to other groups) in low income countries in Africa, and the role of social pensions. This study aims to fill this gap. The findings show much heterogeneity across countries with respect to the proportion of the elderly population, the living arrangements, and the composition of households, and household headship. The analysis shows that the poverty situation, and especially the poverty gap ratio, for the household types the "elderly only", the "elderly with children" and the "elderly-headed households" is much higher than the average in several countries, and the differences are statistically significant. The analysis further shows that the fiscal cost of providing a universal non-contributory social pension to all of the elderly will be quite high - 2 percent to 3 percent of GDP, a level comparable to, or even higher, than the levels of total public spending on health care in some countries. While categorical targeting of a pension for the above groups yields the maximum poverty reduction impacts, and is also fiscally sustainable even in low income countries, its operational feasibility is considered to be weak. The study concludes that the case for a universal approach is weak. The best option appears to be to target the pension only to the poor among the elderly, keeping the benefit level low. The study underscores the need for more country-specific work to explore the feasibility of the recommended option in diverse country settings.